2016
DOI: 10.1038/ajg.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment Predicts The Occurrence Of Hepatic Encephalopathy After Transjugular Intrahepatic Portosystemic Shunt

Abstract: Psychometric evaluation before TIPS is able to identify most of the patients who will develop HE after a TIPS and can be used to select patients in order to have the lowest incidence of this important complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 33 publications
(36 reference statements)
4
57
2
1
Order By: Relevance
“…The incidence of HE reported in the literature varies widely[3]. However, in our study, HE occurred at the same rate at the first year after TIPS creation.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The incidence of HE reported in the literature varies widely[3]. However, in our study, HE occurred at the same rate at the first year after TIPS creation.…”
Section: Discussionsupporting
confidence: 46%
“…The establishment of TIPS has been widely accepted as an alternative to surgery in the management of complications from portal hypertension, such as variceal bleeding, refractory ascites, Budd-Chiari syndrome, hepatorenal syndrome, hepatic hydrothorax and even hepatopulmonary syndrome[2]. After TIPS was introduced as an alternative treatment for complications related to portal hypertension, it has become progressively recognized as an effective therapeutic option in a growing number of clinical situations[3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…32 Different trials investigated the main risk factors of post-TIPS HE which are: history of previous HE, older age, high creatinine levels, low serum sodium and low albumin values, 34 low Portacaval Pressure Gradient (PPG) and Child-Pugh score. 35,36 Two recent studies demonstrated that also minimal HE 37 and sarcopenia pre-TIPS 38 have a strong impact on overt HE development after TIPS placement.…”
Section: Hepatic Encephalopathy After Transjugular Intrahepatic Portomentioning
confidence: 99%
“…Twenty-five were analysed ( Figure 1). The main characteristics are listed in Table 1: median age was 59 years, male gender 76%, median Child-Pugh score = 8 [5][6][7][8], median MELD score = 12 [9][10][11][12][13][14][15][16][17]…”
Section: Clinical Evaluation Before Tipss Placementmentioning
confidence: 99%
“…Prevalence of overt hepatic encephalopathy (OHE) after TIPSS varies among series, reaching up to 50% in older studies where bare TIPSS were placed. 1 With the almost exclusive use of covered stents, this prevalence has decreased but still ranges between 20% and 30% at 1 year, in both controlled [2][3][4][5][6][7] and observational studies. 8,9 A metaanalysis showed that this prevalence was higher after TIPSS than in control group, that is, patients who did not undergo TIPSS placement.…”
Section: Introductionmentioning
confidence: 99%